2016
DOI: 10.4081/ejtm.2016.6059
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of surface motor activation zones in hemiplegic patients during 20 sessions of FES therapy with multi-pad electrodes

Abstract: The purpose of this study was to examine surface motor activation zones for wrist, fingers and thumb extension movements and their temporal change during 20 therapy sessions using advanced multi-pad functional electrical stimulation system. Results from four hemiplegic patients indicate that certain zones have higher probability of eliciting each of the target movements. However, mutual overlap and variations of the zones are present not just between the subjects, but also on the intrasubject level, reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Apart from the limitations previously mentioned, technological advances were made to improve muscle recruitment selectivity. From these, the development of the multifield electrode system enhances the generation of a localized electric field that increases the selectivity in motor units recruitment with reduced discomfort and fatigue [ 74 ], compared to other methods of electrical stimulation [ 18 , 75 ]. Multifield FES systems are developed for various applications [ 74 , 76 ].…”
Section: Ul Post Stroke Rehabilitation Factors That Should Be Conside...mentioning
confidence: 99%
“…Apart from the limitations previously mentioned, technological advances were made to improve muscle recruitment selectivity. From these, the development of the multifield electrode system enhances the generation of a localized electric field that increases the selectivity in motor units recruitment with reduced discomfort and fatigue [ 74 ], compared to other methods of electrical stimulation [ 18 , 75 ]. Multifield FES systems are developed for various applications [ 74 , 76 ].…”
Section: Ul Post Stroke Rehabilitation Factors That Should Be Conside...mentioning
confidence: 99%
“…It can be observed that there is a large standard deviation, which is explained by the well-documented intersubject variability. [10,21] In addition to the inherent intersubject variability, it has been reported that these parameters also greatly vary for each person over time, and also depend on the physiological conditions during the experiment, such as perspiration rate and skin condition (e.g., dryness, natural oils, sweat chemistry, roughness, elasticity, etc.). Further, the experimental conditions are also hard to be precisely controlled, such as the pressure on the electrode or relative position on the forearm, among others.…”
Section: Human Model Equivalent Circuit Parameters Characterizationmentioning
confidence: 99%
“…The optimal electrode configuration for transcutaneous stimulation depends on the electrode-skin interface, skin impedance, and physical characteristics, and is therefore person-specific and changes on a daily basis. [10] Multi-pad electrodes have shown great potential in addressing mentioned problems by allowing flexible control of the underlying neural structures, which results in nature-like muscle activation and movements. [3a] By having a larger number of independent pads that can be activated in a sequence or selected to form a single electrode, [11] in a manner that can be personalized for each user, the multi-pad approach provides a powerful platform for control of current propagation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the often-reported usability issues with commercial FES foot drop devices is the complex initial set-up and the difficulty to find the right electrode positions. 19,20 The latter can be caused by the intra-subject variation of the spatial activation points from day to day 21,22 that complicate the search for proper electrode positions and stimulation parameters valid over multiple unsupervised applications. This type of usability issue may discourage potential users from using FES foot drop devices, 20 so it is important to consider usability aspects from the initial design and development stages of FES systems to be able to improve uptake.…”
Section: Introductionmentioning
confidence: 99%